TERAK NON-BESI SEBAGAI TAMBAH SEMEN PORTLAND PADA BETON STRUKTURAL - Yansiku, Sandy I.; Duran, Yohanes G.G.L. (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The degradation in environmental grade and generating concrete with low level of ordinary Portland cement have emerged intention for researchers to produce concrete with slag-based substitutional material. The utilization of slag as a partial substitution of cementitious material in concrete has encountered the need of more sustainable materials in the concrete technology. In contrast, the application of non-ferrous slag (NFS) as substitution of the ordinary Portland cement is not well focused despite the largely global slag deposit and the application in concrete technology. Worldwidely immense deposit of various non-ferrous slag from mining and manufacturing process can be used in generating high performance concrete. On that account, this paper provides a critical review of recent studies concerning the non-ferrous based slag as the substitution of regular Portland cement. Production techniques, properties and the applications of NFS for high strength concrete are also examined. Cement with nickel and copper slag addition with high silica content has the potential to increase concrete durability with proper curing method due to better hydration process and low porosity. The maximum 15% non-ferrous slag addition in total cement weight at high water cement ratio increases concrete compressive strength by up to 30%. Substitution of non-ferrous slag for the ordinary Poertland cement in concrete has great potential to overcome stock waste issues, to reduce carbon dioxide emission and consequently reduce global energy consumption as an environmentally friendly approach.